The other black girl ebook A novel. - Harris, Zakiya Dalila (2021)
Now a Hulu Original Series "Riveting, fearless, and vividly original" (Emily St. John Mandel, New York Times bestselling author), this instant New York Times bestseller explores the tension that unfurls when two young Black women meet against the starkly white backdrop of New York City book publishing. Twenty-six-year-old editorial assistant Nella Rogers is tired of being the only Black employee at Wagner Books. Fed up with the isolation and microaggressions, she's thrilled when Harlem-born and bred Hazel starts working in the cubicle beside hers. They've only just started comparing natural hair care regimens, though, when a string of uncomfortable events elevates Hazel to Office Darling, and Nella is left in the dust. Then the notes begin to appear on Nella's desk: LEAVE WAGNER. NOW. It's hard to believe Hazel is behind these hostile messages. But as Nella starts to spiral and obsess over the sinister forces at play, she soon realizes that there's a lot more at stake than just her career. Having joined Wagner Books to honor the legacy of Burning Heart , a novel written and edited by two Black women, she had thought that this animosity was a relic of the past. Is Nella ready to take on the fight of a new generation? "Poignant, daring, and darkly funny, The Other Black Girl will have you stressed and exhilarated in equal measure through the very last twist" ( Vulture ). The perfect read for anyone who has ever felt manipulated, threatened, or overlooked in the workplace.